Designing instructional media for English speaking club to develop learners’ communication skills - Bramy Biantoro; Alimin Adi Waloyo; Nina Inayati; Nosa Setia Budi; I. Ibrahim (Universitas Muhammadiyah Malang, 2023)
This paper presents the development of instructional media for an English-speaking club to improve students’ speaking and general communication skills as part of a community service program. This was conducted as an attempt to address a lack of English communication competence of students at SMP Muhammadiyah 1 Malang. The project is part of the collaboration between the English Language Education Department (ELED) of the University of Muhammadiyah Malang (UMM) and SMP Muhammadiyah 1 Malang. The project involved ELED lecturers, students, and English teachers and students of SMP Muhammadiyah 1 Malang. The chosen topics for the English club are relevant to students’ everyday lives, complemented with corresponding English language-related games. For that, a module was created for ten sessions with three specific topics (English vlog, speech, and storytelling), complemented with the digitalized media for the games in each session. This paper presents a detailed account of the preparation, development, and evaluation of the developed module and media for the speaking club, emphasizing the collaborative nature of all involved in the project. Lessons learned are discussed and highlighted for other English language teachers and educators who wish to conduct the same project in their respective institutions.